Gross and Biometrical Studies on Internal Female Genitalia of Adult Bakerwali Goat in Different Phases of Estrus Cycle - Saleem, Rabab; Suri, Shalini; Sarma, Kamal (Indian Journal of Veterinary Anatomy, 2018)
Gross and biometrical study was conducted on internal female genitalia of 50 apparently healthy female non-pregnant cyclic adult (2-3 years of age) Bakerwali goats. After examining the condition of the ovary samples were divided into follicular and luteal phase. Ovaries were almond shaped, firm, ovoid bodies, flattened on both sides, held in mesovarium of broad ligament. The width, thickness of left ovary and length of left oviduct was significantly higher than the right one in luteal phase. The cyclic ovaries presented a number of follicles, corpora lutea and corpora albicantia along their surface. The follicles were more on left ovary than on right ovary. Oviduct comprised of three parts - infundibulum, ampulla and isthmus. The ampullary region was quite tortuous and the isthmus was a comparatively less coiled part of the oviduct. The uterus was bicornuate and bipartite type. It consisted of two uterine horns, body of uterus and cervix uteri. The length of free part of left cornu was higher than the right one in follicular phase of estrus cycle but statistically nonsignificant. The length of the cervix was significantly higher in luteal phase of estrus cycle.